2008
DOI: 10.1038/nn2053
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde regulation of motoneuron differentiation by muscle β-catenin

Abstract: Synapse formation requires proper interaction between pre- and postsynaptic cells. In anterograde signaling, neurons release factors to guide postsynaptic differentiation. However, less is known about how postsynaptic targets retrogradely regulate presynaptic differentiation or function. We found that muscle-specific conditional knockout of beta-catenin (Ctnnb1, also known as beta-cat) in mice caused both morphologic and functional defects in motoneuron terminals of neuromuscular junctions (NMJs). In the absen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
161
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(173 citation statements)
references
References 50 publications
12
161
0
Order By: Relevance
“…5F), both of which are believed to inhibit AChR clustering (37,52). In contrast to the effect of ␤-catenin in cultured muscle cells, a recent report shows that muscle-specific deletion of the ␤-catenin gene resulted in an increase in the size of AChR clusters, probably due to the retrograde effect of muscle ␤-catenin on presynaptic transmitter release (53). It is known that ACh acts to disperse AChR clusters (4,5,8).…”
Section: Discussionmentioning
confidence: 99%
“…5F), both of which are believed to inhibit AChR clustering (37,52). In contrast to the effect of ␤-catenin in cultured muscle cells, a recent report shows that muscle-specific deletion of the ␤-catenin gene resulted in an increase in the size of AChR clusters, probably due to the retrograde effect of muscle ␤-catenin on presynaptic transmitter release (53). It is known that ACh acts to disperse AChR clusters (4,5,8).…”
Section: Discussionmentioning
confidence: 99%
“…In support of the idea that agrin induces the release of a retrograde signal capable of disinhibiting presynaptic specialization, we found that agrin induces FGF expression in muscle and conversely, that muscle from agrin-deficient mice expresses less FGF than muscle from control mice. However, other retrograde factors such as β-catenin are required for antagonizing AChinduced inhibition of presynaptic differentiation such as β-catenindependent signals (51).…”
Section: Discussionmentioning
confidence: 99%
“…Presynaptic defects are supposedly due to lack of proper agrin-induced retrograde signaling from muscle to nerve that accounts for the maturation of the growth cone into a nerve terminal. The intracellular pathways that mediate this signaling are unknown, however, it seems that ␤-catenin is a key player (41). It is tempting to suggest that agrin-induced ERK1/2 activation might be part of a retrograde signaling pathway that regulates pre-synaptic differentiation.…”
Section: Discussionmentioning
confidence: 99%